2021
DOI: 10.2196/20405
|View full text |Cite
|
Sign up to set email alerts
|

Tablet-Based Telerehabilitation Versus Conventional Face-to-Face Rehabilitation After Cochlear Implantation: Prospective Intervention Pilot Study

Abstract: Background Technologies allowing home-based rehabilitation may be a key means of saving financial resources while also facilitating people’s access to treatment. After cochlear implantation, auditory training is necessary for the brain to adapt to new auditory signals transmitted by the cochlear implant (CI). To date, auditory training is conducted in a face-to-face setting at a specialized center. However, because of the COVID-19 pandemic’s impact on health care, the need for new therapeutic setti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
0
19
1
3
Order By: Relevance
“…Results of present study revealed that both the service delivery modalities were successful; however; conventional therapy mode had more impact on speech, language, and auditory skills. Results of the present study is in contrary to the findings of studies conducted by Piron et al, (2008) , Hughes et al, (2012) , Malandraki et al, (2014) , Blosser (2015) , Bush et al, (2016) , Volter et al, (2021) , and Choudhary et al, (2021) . The differences between the findings of the present study and the other studies in the past could be attributed to the age differences of the participants considered.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Results of present study revealed that both the service delivery modalities were successful; however; conventional therapy mode had more impact on speech, language, and auditory skills. Results of the present study is in contrary to the findings of studies conducted by Piron et al, (2008) , Hughes et al, (2012) , Malandraki et al, (2014) , Blosser (2015) , Bush et al, (2016) , Volter et al, (2021) , and Choudhary et al, (2021) . The differences between the findings of the present study and the other studies in the past could be attributed to the age differences of the participants considered.…”
Section: Discussioncontrasting
confidence: 99%
“…In March 2020, the Ministry of Health and Family Welfare (MoHFW) published the revised guidelines for telemedicine service delivery whereas, in October 2020, the Indian Speech-Language and Hearing Association (ISHA) published the guidelines for teleservice in the speech-language pathology and audiology due to COVID-19 pandemic. After COVID-19 outbreak, various studies ( Fritz et al, 2021 ; Chaudhary et al, 2021 ; Tambyraja et al, 2021 ; Volter et al, 2021 ) got published on delivery of teleservices for diverse populations with speech-language disorders and sudden increase in the use of tele-therapy modality was observed in the field of speech-language pathology & audiology services in India ( Aggarwal et al, 2020 ). Chaudhary et al, (2021) compared the outcomes of tele-therapy and conventional face-to-face therapy for various speech-language disorders (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, engagement of external and internal motivation of the user is mandatory for the success of the training [Henshaw et al, 2015;Völter et al, 2020b]. Computer-based training platforms based on modern learning concepts might be a promising way to train with high frequency and fun, independently of time and place [Tuz et al, 2021;Völter et al, 2021a].…”
Section: Discussionmentioning
confidence: 99%
“…Diesen mangelt es häufig an Komplexität, Adaptivität, Feedback-und Motivationselementen [43]. Computerbasierte Trainingsplattformen, die eine standardisierte Online-Hörrehabilitation in Analogie zum Training vor Ort beinhalten, sind noch in der Entwicklung [45]. Videotherapeutische Settings wurden bisher in der Logopädie vornehmlich zur Behandlung sprachtherapeutischer Störungsbilder, wie der Aphasie, Dysphagie, Dysphonie und des Stotterns bei Patienten unterschiedlichen Alters eingesetzt [6,16,22,29,33,34,46].…”
Section: Hintergrundunclassified